Pengembangan Media Pembelajaran Fisika Matematika Materi Transformasi Koordinat Berbasis E-Modul (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
Learning physics mathematics is one of the subjects in the physics education study program at the University of Jambi. Based on the results of the questionnaire, students' needs regarding learning mathematics and physics are considered difficult to understand the material taught by lecturers. This is due to the less varied teaching materials and the books used are only sourced from the book Mathematical Methods in Physics written by Mary L. Boas with a thickness of 839 pages consisting of 15 chapters with the language used in English. This is why this research was conducted with the aim of being able to help students with problems when learning mathematics and physics, especially in the material of coordinate transformation using e-modules created using Flip PDF Professional software. The method used is a mixed method with an explanatory design where quantitative data in the form of questionnaire results are strengthened by qualitative data in the form of interviews. Based on the research results, the existence of e-modules can be an alternative in learning that can be used by lecturers and students who are used for independent study with a flexible design that can be used.